Prognostic relevance of prognostic nutritional indices in gastric or gastro-esophageal junction cancer patients receiving immune checkpoint inhibitors: a systematic review and meta-analysis - Hou, Shufu; Song, Dandan; Hao, Ruiqi; Li, Linchuan; Zhang, Yun; Zhu, Jiankang (Frontiers in Immunology, 2024)
Background The Prognostic Nutritional Index (PNI) has become an important predictive tool for assessing patients’ nutritional status and immune competence. It is widely used in prognostic evaluations for various cancer patients. However, the prognostic relevance of the Prognostic Nutritional Index (PNI) in gastric or gastro-esophageal junction cancer patients (GC/GEJC) undergoing immune checkpoint inhibitors (ICIs) treatment remains unclear. This meta-analysis aimed to determine the prognostic impact of PNI in this specific patient cohort. Methods We conducted a thorough literature search, covering prominent databases such as PubMed, Embase, Web of Science, SpringerLink, and the Cochrane Library. The search spanned from the inception of these databases up to December 5, 2023. Employing the 95% confidence interval and Hazard Ratio (HR), the study systematically evaluated the relationship between PNI and key prognostic indicators, including the objective remission rate (ORR), disease control rate (DCR), overall survival (OS) and progression-free survival (PFS) in GC/GEJC patients undergoing ICI treatment. Results Eight studies comprising 813 eligible patients were selected. With 7 studies consistently demonstrating superior Overall Survival (OS) in the high-Prognostic Nutritional Index (PNI) group compared to their low-PNI counterparts (HR 0.58, 95% CI: 0.47–0.71, P<0.001). Furthermore, the results derived from 6 studies pointed out that the significant correlation between he low-PNI and poorer progression-free survival (PFS) (HR 0.58, 95% CI: 0.47–0.71, P<0.001). Subgroup analyses were performed to validate the robustness of the results. In addition, we conducted a meta-analysis of three studies examining the correlation between PNI and objective response rate/disease control rate (ORR/DCR) and found that the ORR/DCR was significantly superior in the high PNI group (ORR: RR: 1.24, P=0.002; DCR: RR: 1.43, P=0.008). Conclusion This meta-analysis indicates that the low-PNI in GC/GEJC patients undergoing ICI treatment is significantly linked to worse OS and PFS. Therefore, PNI can serve as a prognostic indicator of post-treatment outcomes in patients with GC receiving ICIs. Further prospective studies are required to assess the reliability of these findings. Systematic review registration https://inplasy.com/, identifier INPLASY202450133.